2021
DOI: 10.1002/cap.10164
|View full text |Cite
|
Sign up to set email alerts
|

Coronally Advanced Flap Combined With Sticky Bone and i‐PRF‐Coated Collagen Membrane to Treat Single Maxillary Gingival Recessions: Case Series

Abstract: Introduction Numerous techniques have been reported in the literature for the reconstruction of gingival recession defects. The purpose of this case series was to evaluate clinically and radiographically the efficacy of sticky bone with i‐PRF‐coated collagen membrane in the treatment of gingival recession. Case Series Sixteen patients exhibiting isolated Miller's Class I or II recession in the maxillary esthetic zone were treated using sticky bone (i‐PRF + freeze‐dried bone allograft) with i‐PRF‐coated collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…41 In a separate study, Kapa and colleagues investigated the use of i-PRF to create sticky bone in 16 patients with isolated Miller Class I and II recessions in the maxillary esthetic zone. 42 Clinical evaluation demonstrated that all treated cases achieved an increase in gingival thickness and keratinized tissue width, as TA B L E 1 Leukocyte, platelet, and monocyte concentrations in whole blood, i-PRF, 0.5 mL of C-PRF, and 0.3 mL of C-PRF (represented as 10 9 × cells/L). Note: The final three columns represent the percentage increase in leukocyte, platelet, and monocyte values when compared to baseline controls.…”
Section: Us E Of I-prf In Peri Odontologymentioning
confidence: 95%
See 2 more Smart Citations
“…41 In a separate study, Kapa and colleagues investigated the use of i-PRF to create sticky bone in 16 patients with isolated Miller Class I and II recessions in the maxillary esthetic zone. 42 Clinical evaluation demonstrated that all treated cases achieved an increase in gingival thickness and keratinized tissue width, as TA B L E 1 Leukocyte, platelet, and monocyte concentrations in whole blood, i-PRF, 0.5 mL of C-PRF, and 0.3 mL of C-PRF (represented as 10 9 × cells/L). Note: The final three columns represent the percentage increase in leukocyte, platelet, and monocyte values when compared to baseline controls.…”
Section: Us E Of I-prf In Peri Odontologymentioning
confidence: 95%
“…well as a decrease in periodontal pockets and recessions. 42 Finally, i-PRF was used as an adjunct in subgingival irrigation of SRP in 15 patients with bilateral periodontal pockets (≥5 mm). 43 No differences were reported between the groups.…”
Section: Us E Of I-prf In Peri Odontologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their description of autologous platelet concentrates (APCs), they concluded that in their literature search, APCs alone, as a barrier membrane, are lacking and, therefore, are recommended for future studies. Kim et al [ 36 ] reviewed various coated barrier membranes and reported that PRF-coated collagen membranes increased gingival thickness[ 37 ]. In another recent review on advances in barrier membranes by Yang et al [ 38 ], the authors summarised and described the ideal requirements of a barrier membrane.…”
Section: Evidence Against Prf As Barrier Membranementioning
confidence: 99%
“…In total, 318 patients received treatment with PRF. Parameters examined in the seven studies were probing depth [52][53][54][55], clinical attachment loss [52][53][54][55], gingival recession [52,55], bone fill [52][53][54]56], bone height [53,54,57], percentage of vital bone [58], intrabony component [54], pain, bleeding [56], wound healing, and tooth mobility [53]. Intrabony defects have been treated with a variety of treatment options.…”
Section: Guided Bone Regenerationmentioning
confidence: 99%